The sticking point in the bench press, the squat, and the deadlift: Similarities and differences, and their significance for research and practice - Kompf, J.; Arandjelovic, O. (Sports Medicine, 2017)
Since it was first observed, and especially so in recent years, the phenomenon of the so-called "sticking point" in resistance training has attracted a substantial amount of sports and exercise science research. Broadly speaking, the sticking point is understood as the position in the range of motion of a lift at which a disproportionately large increase in the difficulty associated with continuing the lift is experienced. Hence the sticking point is inherently the performance bottleneck, and is also associated with an increased chance of exercise form deterioration or breakdown. Understanding the aspects of lifting performance which should be analysed in order to pinpoint the cause of a specific sticking point and therefore devise an effective training strategy to overcome it is of pervasive importance to strength practitioners, and is conducive to injury avoidance and continued progress. In this paper, we survey a range of physiological and biomechanical mechanisms which contribute to the development of sticking points, and then, led by this insight, review and analyse the findings of the existing observational research on the occurrence of sticking points in three ubiquitous exercises: the bench press, the squat, and the deadlift. The findings of our analysis should be used to inform future research and current resistance training practice.